CCR5 genotype and plasma ß-chemokine concentration of Brazilian HIV-infected individuals - Mikawa, A. Y. [UNESP]; Tagliavini, S. A. [UNESP]; Costa, P. I. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
The 32-bp deletion in the HIV-1 co-receptor CCR5 confers a high degree of resistance to HIV-1 infection in homozygous individuals for the deleted allele and partial protection against HIV-1 during disease progression in heterozygotes. Natural ligands for CCR5, MIP-1alpha, MIP-1ß and RANTES, have been shown to inhibit HIV replication in CD4+ T cells. In the present study, we examined the CCR5 genotype by PCR and the plasma levels of RANTES and MIP-1alpha by ELISA among blood donors (N = 26) and among HIV-1-infected individuals (N = 129). The control group consisted of healthy adult volunteers and HIV-1-infected subjects were an asymptomatic and heterogeneous group of individuals with regard to immunologic and virologic markers of HIV-1 disease. The frequency of the CCR5 mutant allele (delta32ccr5) in this population was 0.032; however, no delta32ccr5 homozygote was detected. These results could be related to the intense ethnic admixture of the Brazilian population. There was no correlation between circulating ß-chemokines (MIP-1alpha, RANTES) and viral load in HIV-infected individuals. RANTES concentrations in plasma samples from HIV+ patients carrying the homozygous CCR5 allele (CCR5/CCR5) (28.23 ng/ml) were higher than in the control samples (16.07 ng/ml; P<0.05); however, this HIV+ patient group (mean 26.23 pg/ml) had significantly lower concentrations of MIP-1alpha than those observed in control samples (mean 31.20 pg/ml; P<0.05). Both HIV-1-infected and uninfected individuals heterozygous for the delta32ccr5 allele had significantly lower concentrations of circulating RANTES (mean 16.07 and 6.11 ng/ml, respectively) than CCR5/CCR5 individuals (mean 28.23 and 16.07 ng/ml, respectively; P<0.05). These findings suggest that the CCR5 allele and ß-chemokine production may affect the immunopathogenesis of HIV-1.
Keywords: HIV-1; CC chemokine receptor 5; delta32ccr5 Frequency allele; Chemokines